THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON CUSTOMER SATISFACTION FOR TOWER 215 CHIPS - Kamila; Nurasfia; Rahmat Hidayat; Imam Malik (Universitas Efarina, 2022)
This research aims to analyze the influence of product quality and price on customer satisfaction. The research method used is a quantitative method. This research uses Purposive Sampling. The sample in this study consisted of 50 respondents. The data collection instrument uses a questionnaire. The dependent variable is the customer satisfaction variable and the independent variable is product quality, price, namely price, product quality, and customer satisfaction for tower 215 Bireuen chips. The data analysis method used is multiple linear regression. All statements are valid, reliable and normal. The results show that the coefficient of determination (R Square) of the independent variable on the dependent variable is R2 = 0.821 or 82.1%. The independent variable can explain the dependent variable. Research shows that price has a significant effect on customer satisfaction for tower 215 Bireuen chips. This is proven by tcount being greater than ttable (2.523 > 2.014). And product quality has a significant effect on customer satisfaction for tower 215 Bireuen chips. This is proven by tcount being greater than ttable (5.120 > 2.014). Meanwhile, the results of the simultaneous test of price variables, product quality, have a significant influence of fcount 51,639 > ftable 2.58 on customer satisfaction. This shows that, the better the price and product quality provided, the greater the customer satisfaction of tower 215 Bireuen chips.